Listening Sessions to Shape the Innovative NIH ComPASS Common Fund Program to Advance Health Equity. - Brown, Alison G. M.; Winchester, Danyelle; Bynum, Shalanda A.; Amolegbe, Sara M.; Ferguson, Yvonne O.; Flournoy Floyd, Minnjuan; Lawhorn, Collene; Le, Jimmy T.; Lloyd, Jacqueline; Oh, April Y.; Tyus, Nadra; Whitaker, Damiya E.; et al. (American Journal of Public Health, 2024)
The National Institutes of Health (NIH) recognized the need for a research program to address the underlying structural factors that impact health. To inform the development of the NIH Common Fund Community Partnerships to Advance Science for Society (ComPASS) Program, NIH obtained input through community listening sessions. Through its design, ComPASS recognizes the essential role of community organizations as the lead in addressing persistent structural and social challenges to accelerate progress toward advancing health equity. (Am J Public Health. 2024;114(7):685–689. https://doi.org/10.2105/AJPH.2024.307656)